Problems and Solution Strategies of Teacher-Child Interaction in Kindergarten Role Games - Zhong, Guolong; Xie, Yuyi; Wang, Mingxi; He, Maohui (Journal of Educational Research and Policies, 2024)
In kindergarten education, interaction and communication between teachers and young children constitute the core means and realization of educational activities. It is found that the interaction initiation in role play presents significant asymmetry, and young children are often in a passive position; at the same time, there is a relative lack of emotional communication in the game, and young children are difficult to fully experience the fun and emotional resonance of the game. In addition, teachers showed more negative emotions during the game. What's more, teachers' timing and choice of methods in guiding children's play are inappropriate. To address the above problems, this paper proposes corresponding improvement strategies. First, teachers should ensure children's autonomy in play; second, teachers should pay more attention to children's emotional performance and psychological needs in play; at the same time, teachers should endeavor to create a harmonious and enjoyable atmosphere for teacher-child interactions; and lastly teachers should provide targeted guidance at the right time.